Pengaruh Proses Tempa Dingin Terhadap Sifat Mekanik Dan Struktur Mikro Baja Karbon Tinggi Dengan Paduan Rendah 1.92%C-0.73%Cr-2%Ni Berbasis Laterit Untuk Aplikasi Grinding Ball - bill rewata (Sekolah Tinggi Teknik - PLN, 2020)
The development of Indonesia's steel industry is still constrained by the limitations of rawmaterials and energy. In terms of raw materials, Indonesia does not have high levels of ironore in sufficient quantities. The limitation of iron ore will be overcome by the use of lateriteiron (nickel) ore. When melted into steel, this type of ore will produce steel with a nickel contentbetween 2-3%. A number promises the emergence of superior traits, especially for producinghigh strength steel which is very much needed in the construction of infrastructure in Indonesia.The addition of chromium to laterite steel aims to increase strength, hardness, suppleness,wear resistance to rust and acid. Going through the forging process can also cause graindistortion and increase strength and hardness, improve ability. The availability of naturalresources makes laterite ore a potential as a basis for independence to meet national steelneeds. By carrying out hard tests, wear resistance tests, micro tests can be known themechanical properties of Cr-Ni laterite steel.